2020
DOI: 10.1021/acsenergylett.0c00900
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Core–Shell Heterojunction Ta3N5-Nanorods/BaTaO2N Photoanode for Solar Water Splitting

Abstract: Heterostructure-based photoanodes have been investigated to enhance light absorption and promote the generation and extraction of charge carriers for efficient solarto-hydrogen energy conversion. Oxy(nitride) semiconducting materials are promising candidates to harvest the visible solar spectrum; however, the realization of stable and efficient oxy(nitride) heterostructure-based photoanodes remains a challenge. Here, we demonstrate a core−shell heterojunction photoanode of Ta 3 N 5 -nanorods/BaTaO 2 N that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 27 publications
1
70
0
Order By: Relevance
“…In addition to their sufficient earth abundance and stability in water, photoelectrode materials must exhibit solar-to-hydrogen (STH) conversion efficiency of above 10% for their commercial viability 2 . Since the first successful demonstration of water splitting with a TiO 2 photoanode by Honda and Fujishima 3 , extensive research has been focused on strategies to maximize the STH efficiency of inorganic photocatalysts, such as SrTiO 3 , NaTaO 3 , WO 3 , Fe 2 O 3 , BiVO 4 , and Ta 3 N 5 because they are typically earth-abundant compounds and are stable in water [4][5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…In addition to their sufficient earth abundance and stability in water, photoelectrode materials must exhibit solar-to-hydrogen (STH) conversion efficiency of above 10% for their commercial viability 2 . Since the first successful demonstration of water splitting with a TiO 2 photoanode by Honda and Fujishima 3 , extensive research has been focused on strategies to maximize the STH efficiency of inorganic photocatalysts, such as SrTiO 3 , NaTaO 3 , WO 3 , Fe 2 O 3 , BiVO 4 , and Ta 3 N 5 because they are typically earth-abundant compounds and are stable in water [4][5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Prior to photoelectrochemical (PEC) measurements using previously reported protocols, 20,21 the Ta/Ba:Ta 3 N 5 -NRs specimens were uniformly coated with FeNiO x as a co-catalyst (see the EDS elemental map in Fig. S6, ESI †) to prevent photo-corrosion of the NRs surfaces as well as to facilitate the oxygen evolution reaction.…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the PEC performance of the Ta/Ba:Ta 3 N 5 -NRs/ FeNiO x photoanode and compares it with that recently reported by our group for a Ta/Ta 3 N 5 -NRs/FeNiO x photoanode. 20 Fig. S7, ESI † demonstrates that the PEC performance of the Ba:Ta 3 N 5 -NRs photoanode was affected by the Ba precursor concentration and that the best performance was obtained at a concentration of 0.125 M. Since the dimensions of the NRs in the Ba:Ta 3 N 5 -NRs were similar to those of the Ta 3 N 5 -NRs, these materials could be used to examine the effects of Ba doping on the Ta 3 N 5 physical properties and the resultant impact on PEC performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Recently, Domen et al have demonstrated a core-shell heterojunction photoanode of Ta 3 N 5 -nanorods/BaTaO 2 N, generating a stable photocurrent owing to efficient generation and extraction of charge carriers. 31 For the reproducible fabrication of thin films exhibiting controllable thickness on the atomic scale and conformal features, Atomic Layer Deposition (ALD) is a promising technique for the deposition of oxidic precursor layers for subsequent nitridation. 32 In this communication, we demonstrate the synthesis of semi-transparent quaternary photoanodes on the examples of SrTaO 2 N and LaTiO 2 N. First, ALD was explored to obtain semitransparent TaO x N y thin films on conductive n-type GaN substrate.…”
mentioning
confidence: 99%